Marketing Aspects of Vegetables: Comparative Study of Four Regions in East Java and Bali - Joko Mariyono; Hanik A. Dewi; Putu B. Daroini; Evy Latifah; Abu Z. Zakariya; Victor Afari-Sefa (Agriekonomika, 2018)
One of the factors that determines the success or failure of agribusiness is ability of farmers to sell the product. Thus, marketing is an important part of vegetable farming. Good marketing process leads to commercialization, and unsuccessful in this step leads to inadequate income. This study aims to explore the marketing aspects of vegetables using descriptive analysis of vegetable marketing relates issues. The aspects include sources of information, traders, time to sell, use of mobile phone in marketing and the potential constraints.  Marketing characteristics of each region were discussed by comparing and contrasting one to another. Data for this study were gathered from a quantitative investigation of 360 farm households situated in four main vegetable producing regions of rural East Java and Bali, Indonesia. The results show that farmers relied on traders and neighbouring farmers as the trusted sources market information. The ways of farmers to sell the product to the market varied across regions. Commonly, farmers had frequent buyers or costumers to sell the products without any special commitment. In majority, farmers contacted a few of traders to sell the product about three days before harvesting. Highly fluctuation of prices was perceived to be the most important constraint among  other factors limiting good marketing. Thus, there is a need to address such constraints to help farmers to get fairness.